Physiochemical Restrictions of Mineral Zoning of Sediment-Hosted Stratiform Copper Deposit in SW China. (26th February 2018) - Zhang, Yan; Han, Runsheng; Wen, Shuming; Wei, Pingtang
Abstract : The Chuxiong basin, located in southwest China, is well known as a mineralization area of red-bed type copper deposits in China. These deposits are characterized by mineral zoning, which is especially true for the Dayao deposits. The mineral zoning is consistent for both horizontal and vertical zoning; from the base (center) of the ore body to the top (outermost), the mineral zones are from hematite, chalcocite, chalcocite + bornite, and bornite + chalcopyrite to pyrite. We studied the mineral zoning in detail using a thermodynamic phase diagram method, such aslog ⁡ f O 2 -log ⁡ f S 2, pH-log ⁡ f O 2, and pH-Eh, and discussed the constraints on the order of the minerals precipitation under different physiochemical conditions. It is indicated that changes in temperature have little effect on pH and Eh in the formation of minerals. S 2− is stable only below 473 K, and the forming temperature of chalcocite must be below 473 K. In this paper, we also explain the mineral zoning formation mechanism and propose that the main controlling factor of mineral zoning is pH. Because this mineral zoning is widespread in sediment-hosted deposits, studies on this mechanism can considerably promote better understanding of the genesis of ore deposits in order to guide the exploration.